Factors predicting success of vaginal delivery in women with oligohydramnios undergoing induction of labour - Malviya, Ritika; Mahor, Suman; Saranu, Sarada (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2021)
Background: Aim was to study the predicting factors for success of vaginal delivery, in women with oligohydramnios undergoing induction of labour. Methods: An observational study conducted in tertiary care centre Kamineni Hospital in 100 patients in 1-year duration with vaginal misoprostol tablets to predict the success of vaginal delivery in cases, if oligohydramnios undergoing induction of labor. Results: In our study total 100 cases was induced. Among these 81% had successful normal vaginal delivery and 19% had caesarean section delivery. Those who underwent caesarean section, their NST had become non reassuring at any time in labour, provided all supportive measures but their labour was terminated by caesarean section for sake of mother or baby. Conclusions: It is preferable to induce the patients of oligohydramnios at term with continous fetal heart rate monitoring and also variability of the fetal heart rate pattern with uterine contractions.